(untitled) (Palíndromo, 2025)
This text explores the evolution of sound art from its origins to contemporary practice. Focusing on sound installations and sculptures, the author distinguishes the sound instalation art from broader sound art practices. The importance of space in defining sound art is emphasized, contrasting it with music and other audio-based art forms. The text traces the historical development of sound installations, highlighting key figures and movements, while also critiquing recent trends that prioritize technology over spatial experience. A clear distinction is drawn between sound art and sound installation art, with the latter being defined as the creative use of sound as a material within a specific space.